Development and psychometric evaluation of nutrigenomics and personalized nutrition-related knowledge, attitude, and behavior questionnaire in dietetic students and professionals - Panchali Moitra; Janvi Nemani; Saba Madre; Jagmeet Madan (Scientific Reports)
Abstract This study aimed to develop and test the psychometric properties of a questionnaire assessing knowledge, attitudes, and behaviors (KAB) related to nutrigenomics and personalized nutrition (PN) in dietetic students and professionals in India. A literature review, six focus group discussions (n = 37), and nine in-depth interviews guided initial item generation. The face, item, and scale content validity indices were calculated and a cross-sectional sample (n = 297) examined the item difficulty (IDI), item discrimination (DI), and internal consistency. Test-retest reliability was estimated in a sub-sample (n = 64) and confirmatory factor analysis method (CFA) using model fit indices - factor loadings, Tucker Lewis Fit Index, and Root Mean Square Error of Approximation established construct validity. The IDI ranged from 0.60 to 0.72 and the mean Cronbach α was 0.82. The CFA results presented four constructs − 1) knowledge and understanding of nutrigenomics, 2) attitude, and willingness to learn nutrigenomics, 3) behaviors toward gene-based dietary advice, 4) training and confidence to practice PN. The intraclass correlation coefficients for knowledge, attitude, behavior, and training domains were 0.74, 0.83, 0.72, and 0.81. The psychometric evaluation indicated that the 45-item KAB_PN is a valid and reliable instrument to assess students’ and dietitians’ knowledge and perspectives toward nutrigenomics and PN.